Utilizing wheat straw and wheat tailings with beef cows - Peverley, B.; Corah, L.; McKee, M. (Kansas State University. Agricultural Experiment Station, 2011)
Ninety-one Simmental-Hereford and Hereford cows in early gestation were used to compare three rations in a 106-day trial: (1) wheat straw, (2) wheat tailings, and (3) soaked wheat straw. Each was fed to groups of lactation and nonlactating cows. Cows fed the soaked wheat straw and those fed wheat tailings out-gained those on wheat straw by 28 and 16.7 pounds, respectively. All cows’ condition score decreased during the trial period. Two-year-old heifers did not perform as well as the mature cows on the straw rations. Dry cows out-gained the lactating cows on both straw and tailing rations.
Cattlemen's Fate in '78 is known as Cattlemen’s Day, 1978
Keywords: Beef; Wheat straw; Wheat tailings; Gain